Are portable ankle brachial pressure index measurement devices suitable for hypertension screening? - Justyna Janus; Jennifer K Nicholls; Edward Pallett; Matthew Bown; Emma M L Chung (PLoS ONE)
Objective In a large-scale population cardiovascular screening programme, peripheral artery disease (PAD) and hypertension would ideally be rapidly assessed using a single device. The ankle-brachial pressure index (ABPI) is calculated by comparing the ankle and brachial blood pressure (BP). However, it is currently unclear whether brachial BP measurements provided by automated PAD screening systems are sufficiently accurate for simultaneous hypertension screening. Methods Two portable PAD screening devices, the MESI ABPI MD and Huntleigh's Dopplex ABIlity, were evaluated following the European Society of Hypertension International Protocol (ESH-IP) Revision 2010 using a mercury-free sphygmomanometer as a reference device. Results On average, the MESI slightly underestimated brachial systolic blood pressure (BP) with a bias and standard deviation (SD) of -3.5 (SD: 3.3) mmHg and diastolic BP with a bias of -1.5 (SD: 2.3) mmHg. For systolic BP estimates, the Dopplex was more accurate than the MESI with a lower bias of -0.5 (SD: 4.2) mmHg but less precise. The MESI successfully fulfilled all the requirements of the ESH-IP for hypertension screening. The Dopplex device failed the ESH-IP due to the absence of DBP measurements. Conclusions The MESI device appears to be suitable for simultaneous PAD and hypertension screening as part of a preventative care programme. Huntleigh's Dopplex ABIlity failed to pass the ESH-IP validation test. Further clinical trials are underway to assess the use of the MESI for simultaneous screening for hypertension and PAD in a population screening setting.